Implementation of Inclusive Early Childhood Education Policies by Local Governments: A Comparative Case Study of Pontianak City and Mempawah Regency, Indonesia - Asmil Ratna; Diana Diana; Ali Formen (AL-ISHLAH: Jurnal Pendidikan, 2026)
Inclusive Early Childhood Education (ECE) is a key strategy for ensuring equitable educational access for all children, including those with special needs. Although Indonesia has strengthened the regulatory framework for inclusive education, evidence on how local governments implement these policies remains limited. This study examines the implementation of inclusive ECE policies in Pontianak City and Mempawah Regency, Indonesia, and identifies factors contributing to differences in implementation outcomes. A qualitative comparative case study was conducted in two local government contexts. Data were collected through semi-structured interviews with education office officials and school principals, field observations, and document analysis. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, involving data reduction, data display, and conclusion drawing. Trustworthiness was enhanced through triangulation and member checking. The findings reveal substantial differences in policy implementation between the two regions. Pontianak City demonstrates stronger regulatory frameworks, institutional support, and coordinated implementation mechanisms, resulting in more systematic inclusive ECE practices. In contrast, Mempawah Regency remains at an early implementation stage, where practices depend largely on individual institutional initiatives. Major implementation challenges include limited teacher competencies, inadequate professional support, insufficient inclusive facilities, and monitoring systems focused primarily on administrative compliance. The study demonstrates that effective implementation of inclusive ECE depends not only on regulatory commitment but also on the alignment of institutional capacity, human resources, professional support, and quality-oriented monitoring systems. These findings contribute to the literature on local education governance by explaining how variations in implementation capacity influence equitable and sustainable delivery of inclusive early childhood education.